Grass Shrimp (Palaemonetes pugio) as a Trophic Link for Methylmercury Accumulation in Urban Salt Marshes - He, Xiaoshuai; Wallace, William G.; Reinfelder, John R. (Environmental science & technology, 2022)
Grass shrimp (Palaemonetes pugio) represent a potential link in the transfer of methylmercury (MeHg) from salt marsh sediments to transient young-of-the-year (YOY) fish. Across six salt marshes subject to varying degrees of Hg contamination, MeHg concentration in grass shrimp was significantly correlated with MeHg in sediment (p < 0.05, R 2 = 0.81). Bioenergetic models show that grass shrimp alone account for 12–90% of MeHg observed in YOY striped bass and 6–22% of MeHg in YOY summer flounder. Direct accumulation of MeHg from grass shrimp to YOY fish increased with MeHg levels in grass shrimp and sediment. However, in the most contaminated salt marshes with the highest levels of MeHg in grass shrimp and sediment, indirect accumulation of MeHg from grass shrimp by YOY summer flounder, whose diet is dominated by benthic forage fish (mummichog), is predicted to plateau because higher concentrations of MeHg in grass shrimp are offset by a lower proportion of grass shrimp in the mummichog diet. Our results demonstrate that grass shrimp are an important trophic link in the bioaccumulation of MeHg in salt marsh food webs and that MeHg accumulation in YOY fish varies with both the concentration of MeHg in salt marsh sediments and benthic food web structure.